(untitled) (Research, Society and Development, 2022)
Introduction: Cervical cancer is one of the main diseases that affect the female population. Its main causative agent is the Human Papillomavirus (HPV) that affects the cervical region causing lesions that can later develop into cancer. There are some risk factors that contribute to the development of this pathology, among them is the infection caused by the Herpes virus. There are some risk factors such as multiparity, smoking, multiple sexual partners and STIs such as herpes simplex virus that acts as a cofactor in the development of this pathology. The work aims to verify in the databases articles that address the relationship of herpes virus and cervical cancer, as well as to determine other pathologies associated with HPV and to verify the prevalence of infections caused by herpes. Methodology: A search was performed in the Pubmed, Scielo and ScienceDirect databases, in which the data of interest were divided into: Sample size, mean age, type of study, form of diagnosis, infections associated with HPV and results obtained. Results and Discussion: At the end of the search, 14 articles were found that dealt with the proposed topic, addressing various aspects of herpes infection along with HPV and the development of cervical cancer. Conclusion: Although there is no evidence that herpes virus causes cervical cancer, it is remarkable that its association with HPV generates the appearance of precancerous lesions, which can become cancer. It was also observed that herpes virus infection has been growing steadily in different regions and that most cases are caused by type 1 of the disease.